ANTARA ADAT DAN SYARIAT (Studi Tentang Tradisi Mandi Safar di Tasik Nambus, Riau, ditinjau dari Perspektif Islam) - Khoiri Khoiri (Universitas Islam Negeri Ar-Raniry, 2017)
This research paper is aimed to analyze the tradition of Safar Bathing in Lake Nambus according to the Islamic perspective. This is a field research conducted at Tanjung Darul village, Tebing Tinggi Sub-District, Meranti Islands Regency, Riau Province. The research found that Safar Bathing is not stated in the Nash (Quran and Hadist). One additional reference claimed by the local residents in preserving this tradition is that of Sheikh Syafruddin argument in his book entitled